Pengaruh Video Edukasi Cara Pembuatan MP ASI dengan Tingkat Pengetahuan, Sikap dan Perilaku Ibu Terhadap Keberhasilan Pemberian MP ASI Pada Bayi Usia 6 Bulan di PMB Indah Dwi Susanti A.Md.Keb - Etis Fatmala Arum; Dede Sri Mulyana (Universitas Malahayati Lampung, 2024)
ABSTRACT Complementary Food for Breast Milk (MP-ASI) is food or drink that contains nutrients given to infants/children to meet their nutritional needs. MP-ASI is given from 6 months to 24 months of age. Objective of the study to find out the effect of educational videos on how to make MP-ASI with the level of knowledge, attitudes and behavior of mothers on the success of giving MP-ASI to babies aged 6 months at PMB Indah Dwi Susanti, A.Md.Keb. The study used quasi esperimental with purposive sampling with a sample of 30 people. Data techniques are included in uivariate analysis using frequency distribution and bivariate analysis. The results of this study indicate that there is an influence of educational videos on how to make MP-ASI with the success of giving MP-ASI with a knowledge value of p-value 0.002 0.05, attitude with a p-value of 0.001 0.05, and behavior p-value 0.001 0.05. There is a significant influence on educational videos on how to make MP-ASI on the success of giving MP-ASI with the level of knowledge, attitudes, and behavior so that you get success in giving MP-ASI. It is hoped that the educational video will be a reference for the success of making and how to give MP ASI to babies aged 6 months at PMB Dwi Indah Susanti am.Ked. Keywords: Video, Knowledde, Attitude, Behaviour ABSTRAK Makanan Pendamping ASI (MP-ASI) adalah makanan atau minuman yang mengandung gizi diberikan kepada bayi/anak untuk memenuhi kebutuhan gizinya. MP-ASI diberikan mulai umur 6 bulan sampai 24 bulan. Penelitia ini bertujuan untuk mengetahui Pengaruh Video Edukasi Cara Pembuatan Mp Asi Dengan Tingkat Pengetahuan, Sikap Dan Perilaku Ibu Terhadap Keberhasilan Pemberian Mp Asi Pada Bayi Usia 6 Bulan Di PMB Indah Dwi Susanti, A.Md.Keb. Penelitian ini menggunakan quasi esperimental dengan purposive sampling dengan sample 30 orang. Teknik data termasuk dalam analisis uivariat menggunakan distribusi frekuensi dan analisis bivariat. Hasil dari penelitian ini menunjukkan bahwa didapat adanya pengaruh video edukasi cara pembuatan MP ASI dengan keberhasilan pemberian MP ASI dengan nilai pengetahuan p-value 0,002 0,05, sikap dengan nilai p-value 0,001 0,05, dan perilaku p-value 0,001 0,05. Terdapat pengaruh yang signifikan video edukasi cara pembuatan MP ASI dengan keberhasilan pemberian MP ASI dengan tingkat pengetahuan, sikap, dan perilaku sehingga mendapatkan keberhasilan dalam pemberian MP ASI. Kata Kunci: Video, Pengetahuan, Sikap, Perilaku